Effects of transcranial direct-current stimulation on laparoscopic surgical skill acquisition. Issue 2 (13th March 2018) - Ciechanski, P; Cheng, A; Damji, O; Lopushinsky, S; Hecker, K; Jadavji, Z; Kirton, A
Graphical Abstract: Non-invasive brain stimulation has been suggested to enhance acquisition of simple motor skills, however, it has not been examined in the context of complex procedures. Our trial explored the possibility that complex surgical skill learning in medical trainees could be enhanced with non-invasive brain stimulation. We provide novel evidence that this approach is safe, feasible and can potentially enhance skill acquisition during a single session of simulation-based surgical training. Improves skill acquisition in novices Abstract: Background: Changes in medical education may limit opportunities for trainees to gain proficiency in surgical skills. Transcranial direct-current stimulation (tDCS) can augment motor skill learning and may enhance surgical procedural skill acquisition. The aim of this study was to determine the effects of tDCS on simulation-based laparoscopic surgical skill acquisition. Methods: In this double-blind, sham-controlled randomized trial, participants were randomized to receive 20 min of anodal tDCS or sham stimulation over the dominant primary motor cortex, concurrent with Fundamentals of Laparoscopic Surgery simulation-based training. Primary outcomes of laparoscopic pattern-cutting and peg transfer tasks were scored at baseline, during repeated performance over 1 h, and again at 6 weeks. Intent-to-treat analysis examined the effects of treatment group on skill acquisition and retention. Results: Of 40 participants, those receiving tDCS achieved higher mean(s.d.) final pattern-cutting scores than participants in the sham group (207·6(30·0) versus 186·0(32·7) respectively; P = 0·022). Scores were unchanged at 6 weeks. Effects on peg transfer scores were not significantly different (210·2(23·5) in the tDCS group versus 201·7(18·1) in the sham group; P = 0·111); the proportion achieving predetermined proficiency levels was higher for tDCS than for sham stimulation. Procedures were well tolerated with no serious adverse events and no decreases in motor measures. Conclusion: The addition of tDCS to laparoscopic surgical training may enhance skill acquisition. Trials of additional skills and translation to non-simulated performance are required to determine the potential value in medical education and impact on patient outcomes. Registration number: NCT02756052 (https://clinicaltrials.gov/ ).